Learning strategies of general practitioners striving to achieve point-of-care ultrasound competence: a qualitative study. (2nd January 2022) - Andersen, Camilla Aakjaer; Espersen, Marie; Brodersen, John; Thomsen, Janus Laust; Jensen, Martin Bach; Davidsen, Annette Sofie
Abstract: Background: Point-of-care ultrasonography (POCUS) is increasingly used in general practice despite the lack of official educational programmes or guidelines for general practitioners (GPs). Aim: To explore how GPs have learnt to use POCUS and which barriers they have encountered in their learning process. Design and setting: Qualitative study conducted in office-based general practice in Denmark. Methods: Semi-structured interviews were conducted with 13 GPs who had implemented POCUS without supporting guidelines or regulations. Analysis was carried out using systematic text condensation. The interview data for this study were collected along with data used in a previous study. Results: The participating GPs described having composed their own ultrasound education following a continuous learning process. Basic POCUS competences were achieved through formalized training sessions at hospital departments or courses. The GPs further developed and expanded their scanning skills through additional courses and continuous self-study practice on patients often while consulting internet sources, textbooks or colleagues. Lack of available ultrasound courses, supervision, and clinical guidelines together with time constraints and financial aspects were mentioned as barriers to their ultrasound training. Conclusion: This study showed how GPs had composed their own ultrasound education individually and differently, guided by their own experiences and beliefs about good clinical practice. Formalized ultrasound training was considered a prerequisite for achieving basic ultrasound competences while continuous practice was considered paramount to develop and maintain scanning skills. There were several obstacles to overcome in the learning process including lack of supervision, guidance, and opportunity for practicing skills. Key points: Little is known about the educational needs of general practitioners striving to achieve ultrasound competences. General practitioners described using formalized training to achieve basic scanning competences and continuous self-study and practice to further develop their skills. Lack of time, supervision, clinical guidelines and ultrasound courses were considered barriers in the learning process together with financial aspects.